ABDULLAH SIDEK : PENULIS DAN PENDIDIK BERWAWASAN - Amida Abdulhamid; Amida Abdulhamid (Sejarah dan tokoh, 2018)
Literary criticism on the works of Abdullah Sidek, a Malaysian author; collection of articles.